(untitled) (Bangladesh Journal of Bioethics, 2013)
The aim of clinical research is to congregate useful knowledge about the human biology. Benefits to the participants are not the purpose of research, although it does secondarily. Therefore, exploitation of human subjects occurred in clinical research. Many people were harmed and basic human rights were violated as a result of their unwillingness participation in research. There have been many tragedies throughout the history of research involving human subjects. Every period of research scandals have been followed by attempt to initiate some ethical codes to protect the human from clinical research. First of such codes is the Nuremberg Code. Thereafter, Helsinky Declaration, Belmont Report and lastly Obama Commission on Guatemala syphilis study. To remember history is essential so that it’s not repeated again. Knowledge of the history will provide a better understanding to handle the research fairly. Researchers and the healthcare providers have no awareness of the history of ethical requirements for clinical research. Therefore, repetition of scandal is being seen. In addition, there are few sporadic studies on this issue. Formulation of UNIVERSAL rules and regulations is required which will not be limited to a specific tragedy or scandal or the practice of researcher in one country. It will provide common understanding and unique values of the research all over the world, although their application will require adaptation to particular culture, health condition and economic setting. DOI: http://dx.doi.org/10.3329/bioethics.v4i1.14265 Bangladesh Journal of Bioethics 2013; 4(1):20-29